Arabic [ an essential grammar - Abu-Shaqra, Faruq (Routledge essential grammars, 2007)
"Arabic: An Essential Grammar is an up-to-date and practical reference guide to the most important aspects of the language. Suitable for beginners, as well as intermediate students, this book offers a strong foundation for learning the fundamental grammar structures of Arabic. The complexities of the language are set out in short, readable sections and exercises and examples are provided throughout."--BOOK JACKET